Unethical evidence against cattle dignity during loading, transportation anf off-loading by livestock marketers in Ibadan metropolis, Nigeria (2013)
Some activities that showed unethical practices against cattle during loading, transportation and off-loading were considered in this paper. Three major cattle market centres (Akinyele, Bodija and Oranyan) in Ibadan metropolis were used Eighty (80) structured questionnaires were randomly administered to the cattle handlers to collect data on Systems of loading, transportation and off-loading of the animals. Visual observations, head counting and image capturing of the animals on board were made. Cattle were transported by road (100%) using different kinds of vehicle including open roofed trailer, truck, saloon cars and buses with different capacities. Cattle were arranged to stand for days under sun and rain until the final destination. Over 94% of respondents transported their animals in 1-3 days. Also, 60%parked breeds, different sizes, homed and polled cattle together in the same truck during transportation. 3.75%, 5%, 7.5% and 83.75% of handlers respectively transported their cattle in the morning, afternoon evening and at any time of the day. Cattle were loaded and off-loaded by dragging, pulling and pushing. It is concluded that there were no Standard Systems of transportation, loading and off-loading of cattle as animals were exposed to inclement weather and hardship.